Integrating John Locke's Philosophy Through Inquiry-Based Learning in Early Childhood English Education - Ingrita, Ardhia Dava (PROJECT (Professional Journal of English Education), 2025)
The current development of education influenced by various factors including philosophy, including John Locke. On the other hand, global development demand human to master international language. This study explains the implementation of John Locke's philosophy in the Inquiry-Based Learning in Early Childhood English Education. The research uses a qualitative method, including semi-structured interviews with three teachers at TK XYZ in Depok, along with literature review to strengthen the theoretical foundations of John Locke's philosophy. The findings show that IBL for early childhood English education can be integrated with John Locke’s philosophy, which emphasizes freedom, experience, and the integration of moral value. The teachers at TK XYZ integrate moral values as an essential aspect to foster empathy and respect among living beings, encouraging children to become moral indivuals and to improve students contextual understanding in English conversation. This study concludes that Locke’s philosophy provide a foundation for implementing IBL, thereby improving the quality of Early Childhood English Education through the combination of cognitive learning and moral values. This approach demonstrates the potential for integrating Locke's philosophy into modern pedagogical practices, offering insights for English educators to support the balanced growth of children.